Produtividade da soja e resistência mecânica à penetração do solo sob sistema plantio direto no cerrado Brasileiro - Dalchiavon, Flávio Carlos [UNESP]; De Passos E Carvalho, Morel [UNESP]; Nogueira, Débora Cristiane [UNESP]; Romano, Daniele [UNESP]; Abrantes, Fabiana Lima [UNESP]; De Assis, Juliana Teodora [UNESP]; De Oliveira, Mário Sérgio [UNESP] (My University, 2011)
The mechanical resistance to soil penetration can be a negative influence to soybean root growth, greatly affecting its yield. In the agricultural year 2008/2009, in Selviria, Mato Grosso do Sul State, in the Brazilian Savannah, the soybean yield was analyzed in relation to the mechanical resistance to soil penetration, in a Dystropherric Red Latosol (Typic Acrustox) under no-tillage. The main purpose was to select, among the soil attributes, the one that best presented spatial and linear correlation to explain the soybean yield variability. A geostatistical grid was installed to collect the soil and plant data, with 120 sampling points, in an area of 8.34 ha and homogeneous slope of 0.055 m m-1. Thus, in order to support future researches concerning precision agriculture, based on the same soil's attributes used for this study, the values for spatial dependence range should be placed between 38.1 m and 114.7 m. From the linear point of view, the mechanical resistance to soil penetration, when evaluated in the 0.10-0.20 m layer, showed good inverse exponential correlation with the soybean yield. However, from the spatial point of view, the number of pods per plant showed to be a good indicator for soybean yield.
Soybean yield and mechanical resistance to soil penetration under no-tillage in the Brazilian savannah
Keywords: Cone index; Glycine max; Precision agriculture; Soil management; Soybean production components